Pro-environment Attitudes and Worker Commuting Behavior - José Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2023)
The private vehicle is, for most developed countries, the prevalent commuting mode of workers, and one of the main source of CO2 emissions. The choice of the mode of transport for commuting trips clearly depends on individual preferences, and it may be that pro-environmental attitudes and values are related to environmental awareness and minimization of harm to the environment. This paper explores how pro-environmental attitudes and values relate to commuting behaviors, using data from the American Time Use Survey for the period 2003-2019. We focus on the time spent commuting, and on commuting modes. The results show that, net of observable factors, regions in which social attitudes are more pro-environmental are related to longer commuting times, but also to a higher percentage of active commuters and public transit commuters. These results suggest that policies aimed at shifting pro-environmental social values may help in reducing the use of private vehicles and encourage green means of transport, in order to reduce the environmental costs of commuting.
Keywords: A13; Q52; R41; 330; pro-environmental attitudes; commuting time; transport mode; American Time Use Survey; American Values Survey; general social survey